2002
DOI: 10.1242/jcs.00173
|View full text |Cite
|
Sign up to set email alerts
|

Structure of laminin substrate modulates cellular signaling for neuritogenesis

Abstract: Increased neuritogenesis on the acidic matrix seemed to be associated with a higher degree of neuronal differentiation, since cell proliferation was immediately arrested upon plating, whereas on neutral matrices, the cell number increased six-fold within 24 hours. Investigation of the mechanisms mediating neurite outgrowth on each condition revealed that the extensive neuritogenesis observed on the acidic matrix involved activation of protein kinase A, whereas moderate neuritogenesis on neutral laminin was med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
86
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(100 citation statements)
references
References 69 publications
12
86
1
1
Order By: Relevance
“…Deposited on Coverslip-Although laminin aggregates could not be detected in neutral pH at 50 g/ml, we have previously demonstrated that deposits of the aggregated protein became visible when the laminin solution was incubated over the surface of a glass coverslip (11,14). Such deposits were characterized by immunostaining and shown to be morphologically different from others obtained in acidic pH.…”
Section: Effect Of Laminin Fragments On Laminin Matricesmentioning
confidence: 92%
See 2 more Smart Citations
“…Deposited on Coverslip-Although laminin aggregates could not be detected in neutral pH at 50 g/ml, we have previously demonstrated that deposits of the aggregated protein became visible when the laminin solution was incubated over the surface of a glass coverslip (11,14). Such deposits were characterized by immunostaining and shown to be morphologically different from others obtained in acidic pH.…”
Section: Effect Of Laminin Fragments On Laminin Matricesmentioning
confidence: 92%
“…When such explants were platted onto laminin adsorbed in neutral pH, laminin in EDTA, or poly-lysine, there was absolutely no migration or axonal growth. Immunolabeling of the matrices produced at each pH with anti-laminin antibodies revealed major morphological differences between them, whereas the acidic one seemed more flat and organized, which could account for its particular signaling properties to neural cells (11).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…As a major component of basement membrane ECM, laminin has frequently been shown to influence neurite outgrowth both in vitro [42][43][44][45] and in vivo [44,[46][47][48][49] . Laminin forms a sheetlike polymer that is best known for its critical involvement in basal membrane formation.…”
Section: Polymersmentioning
confidence: 99%
“…Laminin Laminin is a heterotrimeric glycoprotein consisting of α, β, and γ subunits that self-assemble in a temperature-, pH-and concentration-dependent manner [41,42] . As a major component of basement membrane ECM, laminin has frequently been shown to influence neurite outgrowth both in vitro [42][43][44][45] and in vivo [44,[46][47][48][49] .…”
Section: Polymersmentioning
confidence: 99%